(untitled) (International Journal of Food and Nutritional Sciences, 2022)
People in India have been dealing with terrible and distressing situations over the past few days. over example, a youngster fell down an uncovered bore well and struck a hole, trapping them. The method of rescuing a trapped child from a bore well is incredibly hazardous and challenging in comparison to other types of catastrophes. The child-saving methods currently in use are also more expensive and less successful. The child needs to be saved for more than a day. Here, the clipper uses a remote controller to pick up and place the youngster who is caught inside the hole in order to save it. The rope that is knotted at its hands manually leaves the cutter within. There would be no need to dig a hole parallel to the bore well in this alternate scenario. Additionally, it has a camera attached to the clipper that is used to watch the youngster. We are able to see the child’s condition thanks to this webcam.